Potential of the Bioaugmentation Method to Enhance the Remediation Process in the Solidification/Stabilization Method - Mohd Rais, Nurul Nasuha; Rachman, Ranno Marlany; Mohd Kamil, Nor Amani Filzah (International Journal of Sustainable Construction Engineering and Technology, 2023)
In the published literature, Stabilization/Solidification (S/S) method was excellent in remediating heavy metals, whereas bioremediation was excellent in remediating organic contaminants. However, tremendous papers only focus on specific contaminants, while the polluted environment is not due to specific contaminants. In this paper, both methods were combined and targeted to remediate both group contaminants, namely organic contaminants and heavy metals. The study focused on the effect of the bioaugmentation method on S/S method with the use of Portland cement as a binder in the S/S method. Sphingobacterium spiritivorum (bacteria) and Aspergillus brasiliensis (fungi) as degrading agents in the bioaugmentation method. The S/S matrices were tested for leaching behaviour which is the concentration of Chemical Oxygen Demand (COD) and heavy metals after 14 and 28 days of hydration. Bacteria augmentation showed a better COD removal compared to without augmentation (S/S method only). Bacteria augmentation also shows better removal compared to fungi augmentation for both hydration days. In addition, by using the S/S method only, COD concentration was increased from 14 to 28 days. For heavy metals, chromium shows a positive result; bacteria augmentation shows the lowest concentration after 14 and 28 days of hydration. While other metals, S/S method only shows the lower concentration compared to samples that augment with bacteria and fungi. Nonetheless, the concentrations of heavy metals in all samples did not exceed the USEPA limit. Therefore, this study contributed to the possibility of combining the S/S and bioaugmentation methods by adding degrading agents to remediate contaminants in the sludge, especially for sludge that contains high organic contaminants.